Improved microstructure, mechanical properties and electrical conductivity of the Cu–Ni–Sn–Ti–Cr alloy due to Ce micro-addition - Tang, Shunlong; Zhou, Meng; Zhang, Yi; Xu, Deye; Zhang, Zhiyang; Zheng, Xianhua; Li, De; Li, Xu; Tian, Baohong; Jia, Yanlin; Liu, Yong; Volinsky, Alex A.; et al. (Materials science and engineering A)
In this paper, new Cu–Ni–Sn–Ti–Cr and Cu–Ni–Sn–Ti–Cr–Ce alloys were prepared and studied. After solution treatment and 60% cold rolling, the Cu–Ni–Sn–Ti–Cr alloy with micro-hardness of 221 HV, a tensile strength of 598.1 MPa, elongation of 9.9% and electrical conductivity of 45.2% IACS was obtained after aging at 500 ◦C for 60 min. Furthermore, the new Cu–Ni–Sn–Ti–Cr–Ce alloy was also obtained using aging at 500 ◦C for 60 min, having 245 HV micro-hardness, 645.2 MPa tensile strength, elongation 9.4% and 44.6% IACS conductivity. The comprehensive properties of high strength, hardness, and electrical conductivity of the alloy are attributed to the composite effects of solution, deformation, grain boundary, and precipitation strengthening. Among them, precipitation strengthening plays a major role, and the precipitates are mainly nanometer CuNi2Ti, Cr, and NiTi phases. The interface between the nanometer CuNi2Ti phase and Cu matrix is a coherent, which can improve the strength of the alloy without sacrificing plasticity. In addition, texture type transformation and texture strength change of the alloy are closely related to the increase of micro-hardness. The micro-addition of trace rare earth Ce can refine the alloy grains, and promote dynamic recrystallization to produce finer grains, significantly improving the alloy’s micro-hardness.